Analysis of Point of Sale System Implementation in Coffee Shop - Irma Hidayati; Sudarmiatin Sudarmiatin; Agus Hermawan (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
The article discusses implementing a point of sale (POS) system in a coffee shop business through a case study method and SWOT analysis. The study shows that the performance of a POS system can significantly improve the efficiency and financial management of the company. The POS system can help inventory management, predict customer demand, and avoid excess or shortage of merchandise stock. It can also speed up the customer payment process, improve customer experience, and generate accurate sales reports. The article concludes that implementing a POS system can be an effective solution for coffee shop businesses to optimize their operations and increase profitability, despite facing challenges and obstacles such as high implementation costs and staff training. Therefore, coffee shop businesses should consider implementing a POS system and ensure that it can be integrated with the existing systems of the business.